2006
DOI: 10.1248/bpb.29.1706
|View full text |Cite
|
Sign up to set email alerts
|

Linear Pharmacokinetics of Micafungin and Its Active Metabolites in Japanese Pediatric Patients with Fungal Infections

Abstract: Development of novel medical products labeled for pediatric use is limited because it is difficult to obtain the safety and pharmacological effect data for the population at the time of approval. The International Conference on Harmonization has issued guidance E11 'clinical investigation of medical products in the pediatric population' to encourage this development. 1) In general, the dosing recommendations for pediatric patients are based on a milligrams per kilogram body weight. However, some drugs are know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 13 publications
(23 reference statements)
4
25
0
1
Order By: Relevance
“…12,21) In the present study, a good correlation was observed between the peak and trough concentrations of MCFG (Fig. 1A) as reported by Nakagawa et al 22) It is worth noting that the similar correlations between the peak and trough concentrations of MCFG are attributable to the fact that patients with severe liver dysfunctions have to provide additional information for the determination of appropriate dose regimens for LDLT-recipients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…12,21) In the present study, a good correlation was observed between the peak and trough concentrations of MCFG (Fig. 1A) as reported by Nakagawa et al 22) It is worth noting that the similar correlations between the peak and trough concentrations of MCFG are attributable to the fact that patients with severe liver dysfunctions have to provide additional information for the determination of appropriate dose regimens for LDLT-recipients.…”
Section: Discussionsupporting
confidence: 89%
“…1B), and this result is comparable to reports concerning patients with hematologic malignancies and pediatrics. [21][22][23] However, when the data obtained from the patients receiving a dose of 300 mg/d MCFG are excluded, the correlation is no longer significant. Additionally, because the correlation between dose and trough concentrations was as a result of a scatterplot, we investigated if other factors correlated with the trough concentration.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of exposure measurements for the two dosing regimens at the steady state is presented in Table 2. As previously shown in other dose escalation studies (26,27), pharmacokinetics increased in a linear manner with dose. Steady-state AUC 0 -48 values for the two dosing regimens were comparable.…”
supporting
confidence: 82%
“…Blood samples were collected from patients just before (trough) and after (peak) micafungin infusion, at least 4 days after initiating treatment (steady state) (2). Micafungin concentration in serum was measured by high-performance liquid chromatography (HPLC) (9,12). The disk diffusion method was performed according to National Committee for Clinical Laboratory Standards (NCCLS) M44-A guidelines (5).…”
mentioning
confidence: 99%